Near-infrared spectrometry for rapid and real-time prediction of specific quality attributes in intact cactus pear fruits (Opuntia ficus-indica L.) - Owino, Willis O.; Lanoi, Daisy; Imathiu, Samuel; Kahenya, Peter; Nyonje, Winnie A.; Yegon, Dennis (Frontiers in Horticulture, 2024)
Cactus pear fruits are rich sources of nutritional (essential vitamins, amino acids and minerals) and antioxidant compounds (flavonoids, carotenes, betalains, ascorbic acid and quercetin). The fruit is cultivated for fresh markets and also serves as nutraceutical and functional food, finding application in various forms such as juice, jam, wine, syrup and in dairy products. However, short postharvest life and negative perception has contributed to its underutilization in the local context. Total titratable acidity (TTA) and total soluble solids (TSS) are among the desirable attributes used to assess postharvest quality of Cactus pears. A portable near-infrared spectrometer (NIRS) can non-destructively determine the internal quality of Cactus pears’ thus reducing postharvest losses. This study evaluated the potential of a handheld NIRS coupled with chemometrics of partial least square regression (PLSR) for rapid, non-destructive, and simultaneous determination of TTA and TSS in intact Cactus pear fruits. Cactus pears at different stages of maturity were sampled from Laikipia county, in Kenya, and immediately subjected to spectral data acquisition and wet-chemistry analyses. The PLSR was used to train and validate predictive models for the determination of TTA and TSS content in intact Cactus pears. The prediction model for TTA gave an R-squared (R2) of 0.73, root mean squared error of prediction (RMSEP) of 0.28% citric acid, and residual predictive deviation (RPD) of 1.97. Additionally, the TSS model resulted in R2 of 0.75, RMSEP of 1.60° Brix, and RPD of 2.06. Overall, these findings highlight the effectiveness of NIRS in non-destructive measurement of TTA and TSS levels in whole Cactus pears. However, with further refinement and optimization of these models, the full potential of this technique for swift and precise assessment of these parameters in whole Cactus pears can be realized. This would greatly benefit farmers and processors by reducing expenses associated with quality assessment and facilitating market entry of Cactus pear derived food products.